Systematic Literature Review: Experience Of Pregnant And Post Partum’s Mother Who Have Baby With Birth Defects - Mahmudah Aji Pamungkas, Atik; Triratnawati, Atik; Utami, Fitria Siswi; Suryantoro, Purnomo (Universitas Muhammadiyah Sidoarjo, 2020)
According to Ministry of Health in 2019infant deaths due to birth defects have increased by 1.4% in newborns with birth defects. Mothers who do not know from the beginning of birth defects experienced by the fetus in their womb can increase the occurrence of postpartum mental health disorders. This occurs because of the unpreparedness of the mother in accepting infants who experience congenital abnormalities.The study aims to review experience of pregnant and post partum’s mother who have babies with congenital abnormalities. The data were searched from Proquest and PubMed. Finally, the researcher found 11 documents that were in accordance with the study criteria. The results was foundthat early prevention of birth defects is needed such as consuming adequate micronutrients, such as folic acid and iodine obtained through additional products or vitamins before and during pregnancy. Early detection are possible to determine the abnormalities in the fetus. Supporting examinations that can be done by mothers such as blood tests, pregnancy ultrasound, and examination of amniotic fluid samples in pregnant women, because the review results state that the incidence of stress of pregnant women who know the diagnosis of birth defects after giving birth is higher than mothers who know the diagnosis during pregnancy.. Conclusion of the study experience of pregnant and post partum’s mother who have babies with congenital abnormalities included that screening and special psychological assistance is needed for pregnant and post partum women with congenital abnormalities’s baby.